Journalists and confidential sources : colliding public interests in the age of the leak - Fernandez, Joseph M. (Abingdon, Oxon ; New York, NY : Routledge, 2021)
Journalists and Confidential Sources explores the fraught and widespread reliance by journalists on anonymous sources, whistleblowers, and others to whom they owe an obligation of confidentiality. It examines the difficulties afflicting such relationships; analyses the deteriorating "right to know" and freedom of expression frameworks; and explores solutions and reforms. The book discusses key Australian and international source protection ethics rules, statutes, court cases, law enforcement actions, and case studies. It highlights weakness in journalists' professional practice codes governing confidentiality obligations; discusses inadequate journalistic appreciation of the importance of establishing clear terms and conditions underpinning confidentiality obligations; and identifies shortcomings in the law governing source protection. The book argues that despite source protection being widely recognised as an important ideal, source protection is under sustained assault, thereby undermining public access to information, and democracy itself. The work focusses on Australia but takes into account source protection in the United Kingdom, the United States, Canada, and New Zealand. This timely contribution to the global discussion on the subject will greatly interest journalists, scholars, educators, and students especially in the areas of media law and policy, journalism, media and communication studies, and public relations; the legal fraternity; and anyone who communicates with journalists.
Part 3 Terminology, minefield, balancing interests, reforms -- 5 Threshold matters -- Introduction -- Different types of journalists' communications with contacts or sources -- More to "sources" than meets the eye -- Attribution, non-attribution, anonymity -- On-the-record, off-the-record, on background -- Anonymous sources and whistleblowers -- Leaks, leakers, and leaking -- Conclusion -- 6 The anonymous sources minefield -- Introduction -- Using anonymous sources without losing audience trust -- Leaks, confidentiality, and political machinations
Part 1: Overview 1. Journalists and their confidential sources 2. Free societies and the struggle for freedom of communication Part 2: Ethics Codes And Law 3. Journalist-source confidentiality and professional practice codes 4. Journalist-source confidentiality and the law Part 3: Terminology, Minefield, Balancing Interests, Reforms 5. Threshold matters 6. The anonymous sources minefield 7. Balancing competing interests 8. Contemplating the way forward Part 4: Conclusion 9. The way ahead
OCLC-licensed vendor bibliographic record.
Keywords: Leaks (Disclosure of information)